Fast field echo resembling a CT using restricted echo-spacing (FRACTURE) sequence for shoulder joint in normal dogs - Ryu, Sanghwa; Park, Soomin; Kim, Eunjee; Woo, Hyeonjae; Jeon, Chang-yeop; Yoon, Junghee; Choi, Jihye (Frontiers in Veterinary Science, 2024)
Shoulder disease is a common cause of forelimb lameness in dogs. Determining the precise underlying cause of shoulder lameness can be challenging, especially in veterinary practice. Computerized tomography (CT) is often the preferred imaging modality for bone evaluation; however, it uses ionizing radiation and provides limited softtissue contrast. Conversely, magnetic resonance imaging (MRI) offers excellent soft-tissue contrast but has limitations in bone imaging. This study aimed to introduce a new technical innovation that enhances cortical and trabecular bone contrast on MRI, which we refer to as Fast Field Echo Resembling a CT Using Restricted Echo-Spacing (FRACTURE). In this prospective pilot study, we aimed to evaluate the use of FRACTURE, CT, and conventional MRI sequences in assessing the normal canine shoulder using a 3.0 Tesla MRI scanner. Five research beagle dogs were included and the following pulse sequences were acquired for each dog: (1) three-dimensional (3D) FRACTURE (2) T2-weighted (T2W) images using 3D turbo spin echo (TSE), (3) T1-weighted (T1W) images using 3D TSE, (4) PD-weighted (PDW) images using 3D TSE, (5) CT. Various parameters, including the delineation of cortical bone (intertubercular groove, greater tubercle, lesser tubercle), conspicuity of the trabecular bone, shoulder joint visualization, and image quality were measured for each dog and sequence. In all sequences, the shoulder joint was successfully visualized in all planes with mild motion artifacts. The intertubercular groove was best visualized on CT and FRACTURE. Both the greater and lesser tubercles were easily identified on CT, FRACTURE, and PDW images. The trabecular pattern scored significantly higher in CT and FRACTURE images compared to T1W, T2W, and PDW images. Overall, the visualization of the shoulder joint was excellent in all sequences except for T1W. The use of FRACTURE in combination with conventional MRI sequences holds promise for facilitating not only soft tissue evaluation but also cortical and trabecular bone assessment. The findings from this study in normal dogs can serve as a foundation for further FRACTURE studies in dogs with shoulder diseases.